Gerenciamento, qualidade e uso da água subterrânea no Campus São Cristóvão, da Universidade Federal de Sergipe - Oliveira, Mayara Mendes Gonçalves de (2024)
Groundwater is a fundamental natural resource not only for living beings but also for the environment, as it meets supply demands for consumption and use, keeps soils moist and provides a guarantee of the base flow of water bodies, maintaining them. perennials in dry or dry seasons. In view of the possibility of using the University's active wells, it is necessary to manage the Campus's underground water and it is also necessary that the water collected is in accordance with the qualitative parameters set out in legislation. Therefore, the objective of this study was to carry out an analysis of underground water management at Campus São Cristóvão (UFS), evaluate the quality of water from active wells and determine whether the evaluated water meets the standards established by legislation. The methodological path of this work was divided into characterization of the study site, analysis of groundwater management at Campus São Cristóvão (UFS), collection and evaluation of water samples from wells and physical-chemical and microbiological analysis of water from wells. Based on the results obtained, it was possible to observe the lack of groundwater management at the São Cristóvão Campus, corroborating the literature, since there is a scarcity of studies on groundwater management in educational institutions. Regarding the physical-chemical and microbiological evaluation, it can be stated that the physical-chemical and microbiological parameters of water for human consumption do not comply with Ministry of Health Ordinance No. 888/2021. Regarding water intended for animal watering, it can be concluded that only well 5 presented sufficient physical-chemical and microbiological quality and could be used for animal consumption. The results obtained for water intended for irrigation showed that only water from wells 5 and 6 has potential for the purpose in question. Finally, based on the analysis carried out regarding water for recreational purposes, it can be concluded that none of the wells have quality potential.